Management of stripe rust of barley using fungicides - P.S. SHEKHAWAT, R.P.S. VERMA and INDU SHARMA, R. SELVAKUMAR*, MADHU MEETA (Indian Phytopathology, 2014)
Under field conditions, various fungicide molecules were validated for their effectiveness on barley stripe rust consecutively for two years under artificial field epiphytotic conditions at two locations. Seven fungicides viz., Propiconazole 25%EC (Tilt @ 0.1%), Tebuconazole 25.9% m/m EC (Folicur @ 0.1%), Triademefon 25%WP (Bayleton @ 0.1%), Propiconazole 25%EC (Tilt @ 0.05%), Tebuconazole 25.9% m/m EC (Folicur @ 0.05%), Triademefon 25%WP (Bayleton@ 0.05%), and Mancozeb 75%WP (Dithane M45 @ 0.2%) with various concentrations were tested for their effectiveness in controlling barley stripe rust severity. All fungicide applications resulted in lower disease severity and higher grain yields than untreated check plots. In Ludhiana, all the fungicides @ 0.1% concentrations reduced disease severity ranging from 83.12% to 92.82% except Dithane M45@ 0.2% (23.18%). In Durgapura, Folicur @ 0.1% and Bayleton @ 0.1% reduced the disease severity to maximum of 83.34% and 85.83% respectively. The average performance of fungicides at both the locations revealed that Bayleton @ 0.1% gave the best per cent disease control to 89.33% followed by Folicur @ 0.1% (87.23%). Significant higher yield was obtained with Bayleton @ 0.1% (65.93 q/ha) followed by Bayleton @ 0.05% (63.97 q/ha).